PHANGS-JWST first results: interstellar medium structure on the turbulent jeans scale in four disk galaxies observed by JWST and the Atacama large millimeter/submillimeter array - Meidt, Sharon E.; Rosolowsky, Erik; Sun, Jiayi; Koch, Eric W.; Klessen, Ralf S.; Leroy, Adam K.; Schinnerer, Eva; Barnes, Ashley T.; Glover, Simon; Lee, Janice C.; Wel, Arjen van der; Watkins, Elizabeth J.; et al. (The astrophysical journal. Part 2, Letters, 2023)
JWST/Mid-Infrared Instrument imaging of the nearby galaxies IC 5332, NGC 628, NGC 1365, and NGC 7496 from PHANGS reveals a richness of gas structures that in each case form a quasi-regular network of interconnected filaments, shells, and voids. We examine whether this multiscale network of structure is consistent with the fragmentation of the gas disk through gravitational instability. We use FilFinder to detect the web of filamentary features in each galaxy and determine their characteristic radial and azimuthal spacings. These spacings are then compared to estimates of the most Toomre-unstable length (a few kiloparsecs), the turbulent Jeans length (a few hundred parsecs), and the disk scale height (tens of parsecs) reconstructed using PHANGS-Atacama Large Millimeter/submillimeter Array observations of the molecular gas as a dynamical tracer. Our analysis of the four galaxies targeted in this work indicates that Jeans-scale structure is pervasive. Future work will be essential for determining how the structure observed in gas disks impacts not only the rate and location of star formation but also how stellar feedback interacts positively or negatively with the surrounding multiphase gas reservoir.